Effects of whey protein hydrolysate on growth promotion and immunomodulation in mouse pups in artificial rearing system. (2nd June 2020) - Takeda, Shiro; Harauma, Akiko; Okamoto, Mariko; Enomoto, Hirofumi; Kudo, Toshiji; Suzuki, Takehito; Mizunoya, Wataru; Moriguchi, Toru
Abstract: This study aimed to investigate the effects of whey protein hydrolysate (WPH) on the growth and immunity of mouse pups in artificial rearing (AR) system. Mouse pups were reared in the AR system with artificial milk including 5% WPH (AR with WPH) or not (AR without WPH), and the remaining pups were reared by their mother (dam) for 14 days after birth. The body weight change and body weight gain rates in the AR with WPH group were significantly higher than those observed in the AR without WPH group and similar to those in the dam group. Moreover the feed and protein efficiencies in the AR with WPH group were significantly higher than those of the AR without WPH group. In addition, the supplement of WPH in the AR system was shown to significantly elevate the number of CD3 + CD8 +, B220 + CD19 +, IA/IE + CD11c +, and CD11b + in the thymocyte and/or splenocyte, and the thymus weight. Furthermore, MALDI‐TOF/MS analysis identified the amino acid sequences corresponding to some peptides, and indicated that VRTPEVDDE had the highest relative intensity among the peptides from tested WPH. Therefore, WPH would be required to not only promote growth, but also exert immunomodulatory activities in mouse pups in AR system.